Plasmodium berghei ookinetes bind to Anopheles gambiae and Drosophila melanogaster annexins. - Kotsyfakis, M; Ehret-Sabatier, L; Siden-Kiamos, I; Mendoza, J; Sinden, R; Louis, C (2005)
Using a proteomic approach we identified polypeptides from Anopheles gambiae and Drosophila melanogaster protein extracts that selectively bind purified Plasmodium berghei ookinetes in vitro; these were two and three distinct polypeptides, respectively, with an apparent molecular weight of about 36 kDa. Combining two-dimensional electrophoresis and MALDI-TOF (matrix-associated laser desorption ionization time of flight) mass spectrometry we determined that the polypeptides correspond to isomorphs of the annexin B11 protein of the fruit fly. When protein extracts derived from A. gambiae and D. melanogaster tissue culture cells were further fractionated, the binding activity matching the annexin protein could be localized in the fraction derived from cell membranes in both diptera. Antibody staining showed that annexin also binds to ookinetes during the invasion of the mosquito midgut. Finally, inclusion of antiannexin antisera in a mosquito blood meal impaired parasite development, suggesting a facilitating role for annexins in the infection of the mosquito by Plasmodium.